The health workforce crisis in Bangladesh: shortage, inappropriate skill-mix and inequitable distribution - Ahmed, Syéd Masud; Hossain, Md Awlad; RajaChowdhury, Ahmed Mushtaque; Bhuiya, Abbas Uddin (© 2011 Ahmed et al; licensee BioMed Central Ltd., 2017)
This article was published in the Human Resources for Health [ © 2011 Ahmed et al; licensee BioMed Central Ltd. ] and the definite version is available at : http://dx.doi.org/10.1186/1478-4491-9-3 The Journal's website is at: http://human-resources-health.biomedcentral.com/articles/10.1186/1478-4491-9-3